2018
DOI: 10.1073/pnas.1803291115
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of estrogen receptor beta augments innate immunity to suppress cancer metastasis

Abstract: Metastases constitute the greatest causes of deaths from cancer. However, no effective therapeutic options currently exist for cancer patients with metastasis. Estrogen receptor β (ERβ), as a member of the nuclear receptor superfamily, shows potent tumor-suppressive activities in many cancers. To investigate whether modulation of ERβ could serve as a therapeutic strategy for cancer metastasis, we examined whether the selective ERβ agonist LY500307 could suppress lung metastasis of triple-negative breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 38 publications
1
53
0
1
Order By: Relevance
“…In vitro studies with TNBC cell lines have shown that ERβ prevents invasiveness but does not affect proliferation (38)(39)(40). Studies with TNBC cell lines showed that ERβ can affect invasiveness by secretion of cystatins (41) and can increase innate immunity (42).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies with TNBC cell lines have shown that ERβ prevents invasiveness but does not affect proliferation (38)(39)(40). Studies with TNBC cell lines showed that ERβ can affect invasiveness by secretion of cystatins (41) and can increase innate immunity (42).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of the ERβ agonist LY500307 in female mice, previously i.v. injected with melanoma cells, decreases lung nodules [55]. Oral administration of TAM [56] and EDX [57] exert inhibitory effects on tumor metastatization into the mouse lungs.…”
Section: Female Hormone Activitymentioning
confidence: 99%
“…Many different cell types express estrogen receptors (α and β ERs) (i.e., epithelial cells, lymphoid tissues and immune cells) that allow estrogen binding and signal activation [82][83][84]. Direct implication of estrogen-dependent effects on innate immunity have been recently evidenced in a syngeneic mouse model of melanoma where in vivo studies showed that the estrogen agonist erteberel, activating the ERβ signaling, was capable of augmenting innate immunity and suppressing lung metastatic colonization by recruitment of antitumor neutrophils to the metastatic niche [55]. On the contrary, castration in male mice led to an increased autoimmune response by the induction of the major histocompatibility complex II (MHCII) [85].…”
Section: Sex and Immunitymentioning
confidence: 99%
“…It must be pointed out that ERβ plays an important role in the cell behavior and extracellular matrix (ECM) composition of breast cancer cells and may have an effect on important chemokine receptors [83,84]. It is also involved in the beclin1-dependent autophagic cascade [85].…”
Section: Roles Of Erβ In Breast Cancer Cell Migration and Invasionmentioning
confidence: 99%